An Empirical Analysis of UCITS and Non-UCITS Funds using the Box-Jenkins Method - Zammit, Francesca (2013)
Abstract This study examines two types of funds, UCITS and non-UCITS using the Box-Jenkins methodology. It set out to decipher the distinguishing characteristics of these two type of funds using the three steps of the Box Jenkins method to arrive at an appropriate ARIMA(p,d,q) model. The process involved experimenting with different ARIMA models to ascertain the best fitting model. The tests revealed compelling evidence in favour of the ARIMA(3,1,4) for all funds except for the Multi-Asset Fund. Furthermore, whilst the original hypothesis could not be established following differentiation, the investigation revealed that the broader the fund is in its diversification of its underlying assets, the more cyclical a fund is found to be. In order to investigate how the individual assets correlate with each other, those that were categorized as cyclical funds were then analysed further. Using their respective financial statements, their underlying assets were examined to establish the cause of the cyclical movements. Significantly, by establishing the existence of cyclical funds, this study contradicts the Efficient Market hypothesis, since if markets are efficient, price cycles cannot be formed. The base data, which utilized fund prices over a period of five years, stretching from 1st April 2008 to 28th March 2013, was provided by the Investment Manager VFM.